MADEN OG GIFTEN: TO SIDER AF SAMME SAG: Et eksempel fra Nias, Indonesien - Wolff, Bente (Tidsskriftet Antropologi, 1998)
Bente Wolff: Food and Poison - a Twosided Coin: An Indonesian Example By using examples from food distribution at everyday occasions and feasts in a tourist area on South Nias Island, food is described as a life substance flowing to the individual from the social relations. This practice among others is both structured by and structuring for the experience of the fundamental principles of life as nourishi.ng substance given to the person by others. Life’s opposite, sickness and death, is then understood within the same logic as mortal substance coming from others, i.e. poison. These two categories are viewed as cultural expressions of the local economic system, but this system is not static. It is argued that poison today is understood as a more depersonalized force than previously, which is itself a result of an increase in commercialized exchange relations.